Physiological, biochemical and microscopic aspects of the rice-Bipolaris oryzae interaction mediated by a strobilurin fungicide - Debona, Daniel (2016)
Strobilurins are among the most important fungicides that are used for plant disease control worldwide. In addition to their fungicide effect, strobilurins can also affect some physiological and biochemical aspects of treated plants. Nonetheless physiological, biochemical and microscopic alterations caused by azoxystrobin (Az), the main marketed strobilurin, in rice crop remain elusive. To address this issue, detailed gas exchange measurements and chlorophyll a fluorescence analysis, antioxidant and defense systems assays as well light microscopy analysis were performed on rice plants (cultivar Metica-1) that were sprayed or non-sprayed with Az (+Fu and -Fu plants) and either challenged or not with Bipolaris oryzae, the causal agent of brown spot. The +Fu non-inoculated plants displayed lower carbon (C) fixation than -Fu plants, and such decrease was not related to photochemical or biochemical limitations but rather to decreased stomatal conductance that limited the CO 2 influx into the mesophyll cells. The photosynthesis of -Fu plants decreased upon B. oryzae infection, which was chiefly governed by photochemical and biochemical limitations. The energy surplus that was caused by limited C fixation in the +Fu inoculated plants was thermally and effectively dissipated until 72 hours after inoculation (hai). For the -Fu plants, however, this mechanism was not sufficient to prevent chronic photoinhibition to photosynthesis. The inoculated plants were not able to fully capture and exploit the collected light energy, but these constraints were greatly limited in the presence of Az. In general, the +Fu plants did not show changes in the activities of antioxidant enzymes, but displayed higher concentrations of reduced glutathione (GSH) than -Fu plants. The activities of superoxide dismutase, peroxidase, ascorbate peroxidase, glutathione peroxidase, glutathione reductase, and glutathione-S-transferase were increased upon B. oryzae infection, but such increases were lower in the +Fu plants. Catalase activity decreased in the inoculated plants compared to the non-inoculated plants regardless of fungicide treatment. The GSH concentration increased in response to the B. oryzae infection, and the +Fu plants sustained higher levels of GSH at advanced stages of fungal infection than did the -Fu plants. The inoculated plants exhibited an extensive oxidative stress as evidenced by higher concentrations of hydrogen peroxide and malondialdehyde compared to the non-inoculated plants, but lower and later increases were recorded in the +Fu plants than in the -Fu plants. The +Fu plants displayed higher activities of β- 1,3-glucanase, peroxidase, polyphenol oxidase (PPO) and lipoxygenase (LOX) in the absence of B. oryzae inoculation and of phenylalanine ammonia lyase, PPO and LOX at 24 hai compared to the -Fu plants. Concentrations of total soluble phenols (TSP) were transiently reduced by fungal infection in the +Fu plants, but such plants presented higher TSP levels at 144 hai relative to their -Fu counterparts. Irrespective of the fungicide treatment, B. oryzae infection increased activities of all defense enzymes studied, but such increases usually were higher for the -Fu plants than for the +Fu plants. Concentrations of lignin thioglycolic acid derivatives were increased following fungal infection in the -Fu plants. Microscopic analyses revealed that hyphae from B. oryzae colonized bulliform, bundle sheath, epidermal, guard, mesophyll and vascular bundle cells besides intercellular spaces, but fewer and smaller fungal cells were noticed in the +Fu than in the -Fu plants. However, the constrained fungal invasion verified in the +Fu plants was not accompanied by amplified defense reactions since cells of the - Fu plants reacted by accumulating phenol-like material, whereas such reaction was only limited in cells of the +Fu plants. Overall, our results showed that Az impaired the photosynthetic performance of non-infected plants by diffusive constraints but prevented, to a greater extent, the damage to the photosynthetic apparatus during the infection process of B. oryzae. In addition, Az reduced B. oryzae-induced oxidative stress by limiting brown spot development rather than by activating the antioxidant system. Although Az had transiently reprogrammed activities of defense enzymes, which may have contributed for explaining the reduced brown spot severity observed in the +Fu plants, its fungicidal activity played a major role in reducing B. oryzae infection.